THE STRENGTH OF SOCIAL CAPITAL OF THE SEKAT BAKAU GROUP IN THE CONSERVATION OF MANGROVE ECOSYSTEMS IN BURUK BAKUL VILLAGE, BUKIT BATU DISTRICT, BENGKALIS REGENCY - Alika Nurmala Siregar; Rina Susanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The damage to the mangrove ecosystem on the coast of Riau, especially in Buruk Bakul Village, which experiences 4 meters of erosion each year, has become a serious environmental problem due to abrasion and land conversion. In response to these conditions, the local community formed the Sekat Bakau Group which focuses on self-help mangrove conservation. This study aims to analyze the typology of the group's social capital in carrying out its conservation role. The approach used is qualitative descriptive, with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that social capital is a strong bond for carrying out conservation actions, consisting of elements of social networks, trust, norms, recognition and proactive actions. The five elements have formed a circle of relationships in the typology of bonding, bridging and linking social capital. The social capital possessed is able to drive conservation actions even though the group has limited economic capital. The results of this study also show the typology of the Sekat Bakau Group's social capital in preserving the mangrove ecosystem, which at the bonding level shows strong internal group membership, at the bridging level there are ties with the community, village government and other conservation groups and at the linking level there are ties and assistance from partners.